Collective emotions and political violence - Clément, Maéva (Manchester University Press, 2023)
This book addresses debates around radicalisation and political violence, and presents a timely analysis of the politics of emotions in narratives of political activism and violence. Drawing on extensive primary data consisting of texts, audios, and videos produced by five Islamist organisations active in the UK in the 2000s and Germany in the early 2010s, the book explores how collective actors move from moderate politics to (violent) extremism. The book develops an innovative theoretical and methodological framework at the intersection of world politics, peace and conflict studies, critical terrorism research, literary studies, and transdisciplinary emotion research. In the first part, Clément problematises previous categorisations of Islamist activism and reconstructs organisations' phases of activism in a data-driven, systematic way. In the second part, the analysis centres on how organisations legitimise changes in activism narratively. Specifically, the book delves into the performance of collective emotions in and through narrative and interrogates their effects on (violent) collective action. By introducing the concept of 'narrative emotionalisation', Clément adds to our understanding of narrative deployments in the context of political violence. While organisations couch radical changes in activism in a strikingly similar romantic narrative, the compared analysis across cases reveals that 'narrative emotionalisation' fully unfolds only in phases of extremism. By exploring how non-state actors manage collective emotions, this book extends beyond the ideology-centric and strategic-rationalist approaches to group radicalisation. It offers an insightful and nuanced account of non-state agency and emotion dynamics in political conflicts.